Identification of distinct secretory patterns and their regulatory networks of ischemia versus reperfusion phases in clinical heart transplantation. (January 2022) - Ledwoch, Nadine; Wiegmann, Bettina; Chichelnitskiy, Evgeny; Wandrer, Franziska; Kühne, Jenny F.; Beushausen, Kerstin; Keil, Jana; Radomsky, Lena; Sommer, Wiebke; Knöfel, Ann-Kathrin; Rojas, Sebastian V.; Ius, Fabio; et al.
Highlights: Distinct inflammatory patterns for ischemic vs. reperfusion phases of HTx. The ischemic signature comprises MIF, OPN, sVCAM-1, sICAM-1, IGFBP-1, SCGF-ß. The reperfusion pattern includes IL-6, sIL-6Rα, IL-1RA, IL-10, sVEGFR-1, HGF, sHer-2. Signatures point to pro-/anti-inflammatory/endothelial biomarker candidates. Signatures may help to identify potential risk constellations according to IRI networks. Abstract: Background: Ischemia/reperfusion injury (IRI) is associated with inflammatory responses contributing to the development of primary graft dysfunction (PGD) and rejection. Here, we investigated the pathophysiology of IRI and the early phase after heart transplantation (HTx) regarding its cytokine/chemokine and endothelial networks. Methods: Using multiplex technology, we assessed protein concentrations in plasma samples of HTx recipients (n = 11) pre-, postoperatively, 24 h and 3 weeks after HTx. The same proteins were quantified in organ storage solutions at the end of heart storage (n = 10). Unsupervised cluster, principal component analysis (PCA), K-nearest neighbor (KNN) network classifier analysis, ANOVA and Spearman correlation analyses were performed to identify specific patterns for IRI and individual kinetics of important soluble factors in HTx. Results: Unique patterns of soluble factors were identified in plasma of HTx patients. KNN analysis defined IL-10, IL-6, sIL-6Rα, IL-1RA, IL-16, sVEGFR-1, IGFBP-1, HGF and sHer-2 as strongest signals directly post-Tx declining 24 hrs after HTx. By contrast, MIF, osteopontin (OPN), sVCAM-1 and sICAM-1, IGFBP-1, SCGF-ß, HGF were highly enriched in organ storage solutions, reflecting distinct ischemic (storage solution) vs. reperfusion (plasma) signatures. Conclusions: We identified specific inflammatory signatures for ischemic vs. reperfusion phases of HTx, associated with pro- as well as anti-inflammatory and endothelial biomarker candidates for IRI. These signatures might help to identify potential danger factors and their networks at both the ex situ (ischemic) as well as the reperfusion phase in the recipient after implantation.